Key bacterial vaginosis-associated bacteria influence each other's growth in biofilms in rich media and media simulating vaginal tract secretions - Lúcia G.V. Sousa; Christina A. Muzny; Nuno Cerca (Biofilm)
Bacterial vaginosis (BV) is a very common gynaecologic condition affecting women of reproductive age worldwide. BV is characterized by a depletion of lactic acid-producing Lactobacillus species and an increase in strict and facultative anaerobic bacteria that develop a polymicrobial biofilm on the vaginal epithelium. Despite multiple decades of research, the etiology of this infection is still not clear. However, some BV-associated bacteria (BVAB) may play a key role in the development of this infection, namely Gardnerella species, Prevotella bivia, and Fannyhessea vaginae. In this work, we aimed to characterize the growth of these three species in a rich medium and in a medium simulating vaginal tract secretions (mGTS). We first assessed planktonic growth in New York City (NYCIII) medium and mGTS and observed that the three species showed distinct capacities to grow in the two media. Surprisingly, despite the ability of all three species to grow in single-species in NYCIII, in a triple-species consortium P. bivia was not able to increase its concentration after 48 h, as assessed by qPCR. Furthermore, when using the more restrictive mGTS media, G. vaginalis was the only BVAB able to grow in the triple-species consortia. Interestingly, we found that P. bivia growth in NYCIII was influenced by the cell-free supernatant (CFS) of F. vaginae and by the CFS of G. vaginalis in mGTS. This antimicrobial activity appears to happen due to the acidification of the media. Single- and triple-species biofilms were then formed, and the growth of each species was further quantified by qPCR. While G. vaginalis had a high capacity to form biofilms in both media, F. vaginae and P. bivia biofilm growth was favored when cultured in rich media. Differences were also found in the structure of triple-species biofilms formed in both media, as assessed by confocal laser scanning microscopy. In conclusion, while all three species were able to grow in single-species biofilms in rich media, in mGTS the growth of G. vaginalis was essential for incorporation of the other species in the biofilm.